The Development of E-Module Using Kvisoft Flipbook Maker Application Based on Case Method in Plane Figures Learning for Fifth Grade Elementary School Students: Indonesia - Simanungkalit, Selsa; Mailani, Elvi; Manurung, Imelda Free Unita; Winara, Winara; Afriadi, Putra (Jurnal Pendidikan Dasar, 2025)
This study aims to determine the validity of the feasibility, practicality, and effectiveness of E-Modules using the kvisoft flipbook maker application based on the case method in flat building learning for grade V of elementary school. The type of development research used is the 4D model consisting of 4 stages, namely, define, design, development, and disseminate. The subjects of this study were 26 people and were students of class VA of Elementary School 174552 Tambunan Balige. Data collection techniques used in this study were observation, interviews and tests with quantitative and qualitative data analysis. The results of the validation assessment by material experts showed a percentage of 80% with a feasible category, the validation assessment by media experts showed a percentage of 80% with a feasible category, and the validation assessment by practitioner experts showed a percentage of 84% with a very practical category. The effectiveness of the e-module is seen from the results of student learning through pre-tests and post-tests which were analyzed using the N-Gain Score calculation and showed a percentage of 56.43% with an effective category. Thus, it can be concluded that the e-learning module that uses the Kvisoft flipbook maker application based on the case method in learning flat shapes is feasible, very practical, and effective for use in the learning process in the classroom